Iron Age Italic population genetics: the Piceni from Novilara (8th-7th century BC) - Patrizia Serventi; Chiara Panicucci; Roberta Bodega; Sara De Fanti; Stefania Sarno; Manuel Fondevila Alvarez; Francesca Brisighelli; Beniamino Trombetta; Paolo Anagnostou; Gianmarco Ferri; Antonino Vazzana; Chiara Delpino; et al. (Taylor & Francis Group, 2018)
Background: Archaeological data provide evidence that Italy, during the Iron Age, witnessed the appearance of the first communities with well defined cultural identities. To date, only a few studies report genetic data about these populations and, in particular, the Piceni have never been analysed. Aims: To provide new data about mitochondrial DNA (mtDNA) variability of an Iron Age Italic population, to understand the contribution of the Piceni in shaping the modern Italian gene pool and to ascertain the kinship between some individuals buried in the same grave within the Novilara necropolis. Subjects and methods: In a first set of 10 individuals from Novilara, we performed deep sequencing of the HVS-I region of the mtDNA, combined with the genotyping of 22 SNPs in the coding region and the analysis of several autosomal markers. Results: The results show a low nucleotide diversity for the inhabitants of Novilara and highlight a genetic affinity of this ancient population with the current inhabitants of central Italy. No family relationship was observed between the individuals analysed here. Conclusions: This study provides a preliminary characterisation of the mtDNA variability of the Piceni of Novilara, as well as a kinship assessment of two peculiar burials.